Penentuan Skala Prioritas Pengembangan Smart Campus Menggunakan Metode AHP - Wirasta, Wendi; Setiarini, Siti Dwi (JURIKOM (Jurnal Riset Komputer), 2021)
Smart Campus is a trend nowadays that allows educational institutions to make various breakthroughs, one of which is combining smart technology with infrastructure to get services, decisions, and sustainability.Â  The research aims to determine the aspects that will be the priority of several components towards or get priority rankings for implementation towards a smart campus. The priority measurement of several smart campus components uses the AHP model which is able to compare and evaluate several scales. The comparison process is carried out using a rating scale based on the point of view of one of the top management on campus as a stakeholder. The methods used are literature study, questionnaire distribution, scale calculation, and priority scale recommendations. The results showed that the calculation of the criteria matrix and alternative matrices were able to produce value ratings, the People Management System aspect became the first priority alternative by 31%. The abstraction level approach can be calculated using the AHP model to get the priority scale for smart campus development